Estimation of Genotype×Environment Interaction and Stability Analysis of Carrot (Daucus carota L.) Genotypes under Different Nutrient Management Systems - Praanjal, P.; Jana, J. C.; Roy, S. K.; Kumar, Prince (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during rabi season (October to March), 2022–23 and 2023–24 at the Horticultural Instructional Farm, Uttar Banga Krishi Viswavidyalaya, Pundibari, West Bengal, for evaluating 24 carrot genotypes under various nutrient management systems. 24 carrot genotypes under various nutrient management systems were evaluated to identify those with greater stability and adaptability for over two consecutive years. Pooled ANOVA results indicated significant differences among all yield and quality traits studied in carrot. AMMI ANOVA further revealed that genotype-×-environment interactions (GEI) significantly influenced the traits. Environmental effects were the major contributors to total variation across all traits, with notable genotype-×-environment interactions. AMMI analysis effectively captured these interactions, aiding in the identification of stable and high-performing genotypes. Based on lower AMMI stability values (ASV) and yield stability index, genotypes G9, G10, G12, and G2 consistently exhibited both high mean performance and stability across traits. Conversely, genotypes G24, G5, and G21 frequently showed poor performance and low stability. Therefore, G9 and G10 were recommended as the most stable and high-performing genotypes across environments. The GGE biplot analysis was done on b-carotene content and yield which also confirmed the stability and adaptability of these genotypes. The environments E5 and E6 performed well for genotype evaluation. G9 and G10 were recommended for breeding and cultivation in a range of growing conditions.